Biomechanical Strain Exacerbates Inflammation on a Progeria‐on‐a‐Chip Model. Issue 15 (17th February 2017) - Ribas, João; Zhang, Yu Shrike; Pitrez, Patrícia R.; Leijten, Jeroen; Miscuglio, Mario; Rouwkema, Jeroen; Dokmeci, Mehmet Remzi; Nissan, Xavier; Ferreira, Lino; Khademhosseini, Ali
Abstract : Organ‐on‐a‐chip platforms seek to recapitulate the complex microenvironment of human organs using miniaturized microfluidic devices. Besides modeling healthy organs, these devices have been used to model diseases, yielding new insights into pathophysiology. Hutchinson‐Gilford progeria syndrome (HGPS) is a premature aging disease showing accelerated vascular aging, leading to the death of patients due to cardiovascular diseases. HGPS targets primarily vascular cells, which reside in mechanically active tissues. Here, a progeria‐on‐a‐chip model is developed and the effects of biomechanical strain are examined in the context of vascular aging and disease. Physiological strain induces a contractile phenotype in primary smooth muscle cells (SMCs), while a pathological strain induces a hypertensive phenotype similar to that of angiotensin II treatment. Interestingly, SMCs derived from human induced pluripotent stem cells of HGPS donors (HGPS iPS‐SMCs), but not from healthy donors, show an exacerbated inflammatory response to strain. In particular, increased levels of inflammation markers as well as DNA damage are observed. Pharmacological intervention reverses the strain‐induced damage by shifting gene expression profile away from inflammation. The progeria‐on‐a‐chip is a relevant platform to study biomechanics in vascular biology, particularly in the setting of vascular disease and aging, while simultaneously facilitating the discovery of new drugs and/or therapeutic targets. Abstract : A progeria‐on‐a‐chip model is engineered to recapitulate the biomechanical dynamics of vascular disease and aging. The model shows an exacerbated injury response to strain and is rescued by pharmacological treatments. The progeria‐on‐a‐chip is expected to drive the discovery of new drugs and to elucidate the role of strain in vascular aging and disease.